Deceased (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1917)
Elected Died 1895 *ABBOTT, AI ATTHUR 1908 1882 *ABBOTT, ARTHUR V 1906 1905 * ABE, MASAYOSHI 1909 1903 * ADAMS, CHARLES C. 1905 1905 * ADAMS, WILLAMS 1909 1903 * ADAMS, W. EDWARDS 1910 1884 *ADDY, MATTHEW 1896 1889 * AKERS, WILLIAMS 1906 1894 *ALLEN R B 1896 1905 * ALLEN, R. SCOTT 1906 1874 *AMIOT, H 1892 1886 *AMSLER, CARL 1894 1895 *ÅNGSTROM, CARL 1901 1887 * ARCHBALD, JAMES 1910 1900 * ARLETT, GEORGE H 1906 1895 *ARMSTRONG, JOHN F 1898 1882 *ARNOLDS, HUGO 1886 1875 *ASHBURNER, CHARLES A 1889 1872 *ASIIBURNER, WILLIAM 1887 1883 *ATKINS, C M , JR 1885 1905 * AUSTEN, PETER T 1907